2019
DOI: 10.1002/cbin.11102
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin stimulates the osteogenic differentiation of rat calvarial osteoblasts by activating the IGF1R/PI3K/Akt signaling pathway

Abstract: Calycosin has been reported to have a strong osteogenic activity and a positive correlation with anti‐osteoporosis effects. However, its precise mechanism of action remains unclear. Since insulin‐like growth factor 1 receptor (IGF1R) signaling and phosphatidylinositol 3‐kinase/Akt (PI3K/Akt) signaling have been shown to play a pivotal role in regulating osteogenesis, we hypothesized that the osteogenic activity of calycosin is mediated by these signaling pathways. Rat calvarial osteoblasts (ROBs) were cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
3
26
0
1
Order By: Relevance
“…Effect of Ga ions on the Akt signaling pathway in osteoblasts. Based on the key roles of the akt signaling pathway in regulating ALP activity (26,27), the influence of Ga ions on the akt signaling pathway in osteoblasts was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of Ga ions on the Akt signaling pathway in osteoblasts. Based on the key roles of the akt signaling pathway in regulating ALP activity (26,27), the influence of Ga ions on the akt signaling pathway in osteoblasts was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the key roles of the Akt signaling pathway in regulating ALP activity ( 26 , 27 ), the influence of Ga ions on the Akt signaling pathway in osteoblasts was investigated. MC3T3-E1 osteoblasts were cultured in osteogenic induction medium with or without GaN (10 −4 M) for 0, 7 or 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that the Sr 2+ -substituted HA hexagon-like microarray obviously promoted the expression of BMP2. Furthermore, the expression level of BMP2 is closely related to cell osteogenic ability and BMP2 can activate the transcription of RUNX2 and Osterix [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a significant transcription factor in the early stage of osteoblast differentiation and bone formation, Osterix can regulate the expression of bone-specific matrix protein- associated genes, such as ALP and OCN, and ultimately promote matrix mineralization [ 40 , 46 ]. When cells were cultured on the scaffold surface for 4 days, the expression level of Osterix was significantly higher in the 4Sr-HA group and the 8Sr-HA group than in other groups ( Figure 9 E); At 7 days, the expression level of Osterix was still significantly increased in the 8Sr-HA group, which may be related to the higher release rate of Sr 2+ in the 4Sr-HA group and the 8Sr-HA group.…”
Section: Resultsmentioning
confidence: 99%
“…An intragenic IGF-1R deletion that was identified in a patient presented short stature ( Harmel et al, 2013 ). IGF-1R signaling, which is activated by IGF-1, plays an essential role in cell growth and development, as well as in bone formation via osteoblast-mediated bone mineralization ( Fang et al, 2019 ). IGF-1R is also involved in bone matrix mineralization.…”
Section: Introductionmentioning
confidence: 99%